Spinning silver - Novik, Naomi (New York : Del Rey, 2018)
"A fresh and imaginative retelling of the Rumpelstiltskin fairytale from the bestselling author of Uprooted, called "a very enjoyable fantasy with the air of a modern classic" by The New York Times Book Review. Miryem is the daughter and granddaughter of moneylenders, but her father is not a very good one. Free to lend and reluctant to collect, he has left his family on the edge of poverty--until Miryem intercedes. Hardening her heart, she sets out to retrieve what is owed, and soon gains a reputation for being able to turn silver into gold. But when an ill-advised boast brings her to the attention of the cold creatures who haunt the wood, nothing will be the same again. For words have power, and the fate of a kingdom will be forever altered by the challenge she is issued. Channeling the heart of the classic fairy tale, Novik deftly interweaves six distinct narrative voices--each learning valuable lessons about sacrifice, power and love--into a rich, multilayered fantasy that readers will want to return to again and again"--
"A fresh and imaginative retelling of the Rumpelstiltskin fairytale from the bestselling author of Uprooted, called "a very enjoyable fantasy with the air of a modern classic" by The New York Times Book Review. Miryem is the daughter and granddaughter of moneylenders, but her father is not a very good one. Free to lend and reluctant to collect, he has left his family on the edge of poverty--until Miryem intercedes. Hardening her heart, she sets out to retrieve what is owed, and soon gains a reputation for being able to turn silver into gold. But when an ill-advised boast brings her to the attention of the cold creatures who haunt the wood, nothing will be the same again. For words have power, and the fate of a kingdom will be forever altered by the challenge she is issued"--
Keywords: FICTION / Fantasy / Epic; FICTION / Fairy Tales, Folk Tales, Legends & Mythology; FICTION / Action & Adventure; Fantasy fiction